Unveiling the Forgotten Stage: Form, Function, and Cultural Negotiation in the Performing Arts of Teater Abdul Muluk, Jambi - Oky Akbar; Sahid Teguh Widodo; Muhammad Rohmadi (Harmonia: Journal of Arts Research and Education, 2026)
Teater Abdul Muluk (TAM) in Jambi remains under-researched in academic discourse despite its enduring practice and sustained preservation by local communities. Unlike Malay theatre in other regions, which has a well-established historiography and receives institutional support, TAM is often regarded as a marginal form within performing arts discourse. This research aims to re-examine this position by interpreting TAM as an active, reflective, and contextual cultural practice, a field for the production of meaning and cultural authority outside canonical centers. This study employs a critical ethnographic approach through performance documentation, in-depth interviews with multi-generational practitioners, and an analysis of performative elements, including staging structures, characterization, props, and music. The findings indicate that the continuity of TAM relies on performative negotiations that converge Malay customs, Islamic ethics, humor, and colonial memory, rather than the mere textual reproduction of the Syair Abdul Muluk. A key finding is the utilization of minimalist props, specifically the table and rattan, which serve as symbolic control centers to regulate authority, sound, the actors’ bodies, and the dramatic flow. These props establish a distinct performative character that defines Malay theater expression in Jambi. This article provides an empirical and methodological foundation for further research to uncover the dynamics of Malay theater practices in regions that have historically been underrepresented in the historiography of the performing arts.